Revolutionizing Profitability and Liquidity Analysis in India's Auto Two and Three-Wheeler Industry: A Comprehensive Study of Hero Motocorp, Bajaj Auto and Tvs Motor - Ajmera Tushar Rameshbhai (Journal of Social Commerce, 2023)
The primary objective of a business organization is to maximize profits and fulfill its short-term financial obligations within a year. The generation of profit is a fundamental aspect of any business organization, and liquidity plays a crucial role in facilitating this process. The attainment of an organization's desired objectives is heavily reliant on its ability to maintain profitability and liquidity. This empirical study aims to identify the profitability and liquidity of companies in the auto two and three wheelers industry that are listed on the stock exchange. The study should encompass the time period from 2011-12 to 2018-19, during which three companies will be randomly selected for the purpose of analysis and findings. The study found that Baja Auto demonstrated a relatively favorable level of profitability, while Hero Motorcorps exhibited a comparatively higher ratio among the selected companies. The comparative liquidity position of Hero Motorcorps and Bajaj Auto appears to be better than that of TVS Motors. Regarding the statistical test of ANOVA, it was found that all selected ratios, except for the Debtors Turnover Ratio, were rejected. This indicates that the selected companies did not exhibit a significant difference in their Debtors Turnover Ratio during the study period.